GENISTEIN INDUCED ALTERATIONS OF THE TESTICULAR BIOCHEMISTRY AND HISTOMORPHOLOGY OF ADULT MALE MICE, MUS MUSCULUS. - ARUNIMA DATTA BANIK; SHUSHOVAN BANIK; VINOY K SHRIVASTAVA (International Journal of Pharma and Bio Sciences, 2013)
Thirty male Mus musculus were divided into two groups of 15 animals each, where the controls received vehicle only and the experimental animals had 10mg/kg body weight genistein /day orally (dissolved in 1:4 DMSO:PBS-vehicle) for 30, 60 and 90 days . Biochemical analyses of testicular phosphatase enzymes (ACP and ALP), protein, cholesterol, glucose and fructose as well as hormone estimations (LH, FSH and Testosterone) reported less steroidogenic activities and low sperm maturity (p<0.001, via two-way ANOVA analysis). Along with these the histo-pathological investigations of testes illustrated that there had been low spermatogenic activities in the treated groups with more severity at the later part of the experiments which suggests that genistein may lead to reproductive insufficiency in adult male mice, in terms of lesser availability of mature spermatozoa. The alterations observed may be under the direct influence of testosterone and unavailability of the gonadotropins or may be via hypothalamo-hypophysial testicular axis.